DEVELOPMENT OF CERTAIN EXTENDED SHAPES AND IMPAIRMENTS IN THEM (Scientific journal of the Fergana State University, 2025)
The article studies the expanded parts of complex forms between morpheme level units, the changes that have occurred as a result of historical development. Although the expansion of complex forms is not common, it is a phenomenon that exists in the language. In the study, some of the expanded forms are analyzed and the discrepancies that occur in them are scientifically substantiated.